2011
DOI: 10.1002/dys.435
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Behavioural Correlates of Coherent Motion Perception in Dyslexia

Abstract: Coherent motion perception was tested in nine adolescents with dyslexia and 10 control participants matched for age and IQ using low contrast stimuli with three levels of coherence (10%, 25% and 40%). Event-related potentials (ERPs) and behavioural performance data were obtained. No significant between-group differences were found in performance accuracy and response latencies of correct responses, for early (P1, N1, and P2) or late (P3) ERP peaks. However, attenuated early ERPs in the 10% coherent condition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…However, these factors do not seem to fully account for the present findings, particularly N170 and P3 results. For example, past research has showed that increased numerosity may augment N170 41 or leave P3 unaffected 42 , and increased motion coherence may induce larger P3 43,44 , all of which were different from what we found in the current study. Therefore, instead of “low-level” factors of numerosity or coherence of motion, “high-level” factors such as perceived reliability may be a more reasonable explanation, in line with the possible evolutionary importance of majority’s gaze that indicates food locations or resources for survival 6 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, these factors do not seem to fully account for the present findings, particularly N170 and P3 results. For example, past research has showed that increased numerosity may augment N170 41 or leave P3 unaffected 42 , and increased motion coherence may induce larger P3 43,44 , all of which were different from what we found in the current study. Therefore, instead of “low-level” factors of numerosity or coherence of motion, “high-level” factors such as perceived reliability may be a more reasonable explanation, in line with the possible evolutionary importance of majority’s gaze that indicates food locations or resources for survival 6 .…”
Section: Discussioncontrasting
confidence: 99%
“…Jednoróg et al (2011) did not find any overall group differences in coherent motion evoked responses, but reported that while control participants (n=16) had a higher N2 peak for coherent motion than random motion, the N2 peak did not differentiate between the two types of motion in dyslexic participants (n=16). Taroyan et al (2011) also reported no significant differences in visual evoked responses between typically developing (n=10) and dyslexic (n=9) adolescents. Similarly, Scheuerpflug et al (2004) found no significant differences in visual evoked potentials between dyslexic (n=16) and typically developing (n=15) children.…”
Section: Introductionmentioning
confidence: 90%
“… 49) Taroyan et al . 20) also reported larger right hemisphere P300 amplitudes in participants with dyslexia during a visual attention task. Breznitz and Leikin 41) suggested that a significant increase in P300 amplitude seems to improve sentence comprehension when processing words with different syntactic functions.…”
Section: Discussionmentioning
confidence: 80%
“…Taroyan et al . 20) investigated correlations related to motion perception in dyslexia by recording ERPs in response to random-dot stimuli that combined low contrast. They found that the P3 amplitude was increased in the right hemisphere of both the dyslexic and control groups.…”
Section: Introductionmentioning
confidence: 99%